On Shared Prosperity in the Middle East and North Africa - Ianchovichina, Elena (World Bank, Washington, DC, 2014)
The Middle East and North Africa (MENA) region has made steady progress in terms of the World Bank's twin goals of eliminating extreme poverty and boosting shared prosperity. During the 2000s, the percentage of people living on less than $1.25 a day declined in all regional economies, except Yemen, and in 2010 was low on average. The incomes of the bottom 40 percent have been growing at higher rates than average incomes in almost all MENA countries. In fact, in terms of the income growth among the bottom 40 percent, the MENA region has done better than most other regions, except Latin America and the Caribbean. Income inequality has not worsened and has been low by international standards. Two things must be done to boost real shared prosperity in the MENA. First, leveling the playing field is a priority because everyone must have a fair opportunity for success. Regulations should not favor the privileged. Second, citizens should hold the state accountable, rather than the other way around. By collecting information and sharing it with the public, citizens will be empowered to act and improve chances of achieving real shared prosperity in the MENA.